Developing a community driven sustainable model of maternity waiting homes for rural Zambia. (October 2016) - Lori, Jody R.; Munro-Kramer, Michelle L.; Mdluli, Eden Ahmed; Musonda (Mrs.), Gertrude K.; Boyd, Carol J.
Abstract: Background: maternity waiting homes (MWHs) are residential dwellings located near health facilities where women in the late stages of pregnancy stay to await childbirth and receive immediate postpartum services. These shelters help overcome distance and transportation barriers that prevent women from receiving timely skilled obstetric care. Objective: the purpose of this study was to explore Zambian stakeholders' beliefs regarding the acceptability, feasibility, and sustainability of maternity waiting homes (MWHs) to inform a model for rural Zambia. Design: a qualitative design using a semi-structured interview guide for data collection was used. Setting: two rural districts in the Eastern province of Zambia. Participants: individual interviews were conducted with community leaders ( n =46). Focus groups were held with Safe Motherhood Action Groups, husbands, and women of childbearing age in two rural districts in Zambia ( n =500). Measures: latent content analysis was used to analyze the data. Findings: participants were overwhelmingly in support of MWHs as a way to improve access to facility-based childbirth and address the barrier of distance. Data suggest that participants can describe features of high quality care, and the type of care they expect from a MWH. Stakeholders acknowledged the need to contribute to the maintenance of the MWH, and that community involvement was crucial to MWH sustainability. Key conclusions: access to facility childbirth remains particularly challenging in rural Zambia and delays in seeking care exist. Maternity waiting homes offer a feasible and acceptable intervention to reduce delays in seeking care, thereby holding the potential to improve maternal outcomes. Implications for practice: this study joins a growing literature on the acceptability, feasibility, and sustainability of MWHs. It is believed that MWHs, by addressing the distance and transportation barriers, will increase the use of skilled birth attendants, thereby reducing maternal and neonatal morbidity and mortality in rural, low resource areas of Zambia. We recommend that any initiative, such as MWHs, seeking to increase facility-based births with a skilled birth attendant also concurrently addresses any local deficiencies in quality of care. Highlights: Maternity waiting homes (MWHs) have been identified as a strategy to overcome the 'distance' issue in facility childbirth. Community driven priorities must be considered for acceptability, feasibility and sustainability when developing a MWH model. Acceptability and sustainability of MWHs appears to be conditional on quality care being available at health facilities.